2018
DOI: 10.3390/md16100367
|View full text |Cite
|
Sign up to set email alerts
|

APS8 Delays Tumor Growth in Mice by Inducing Apoptosis of Lung Adenocarcinoma Cells Expressing High Number of α7 Nicotinic Receptors

Abstract: The alkylpyridinium polymer APS8, a potent antagonist of α7 nicotinic acetylcholine receptors (nAChRs), selectively induces apoptosis in non-small cell lung cancer cells but not in normal lung fibroblasts. To explore the potential therapeutic value of APS8 for at least certain types of lung cancer, we determined its systemic and organ-specific toxicity in mice, evaluated its antitumor activity against adenocarcinoma xenograft models, and examined the in-vitro mechanisms of APS8 in terms of apoptosis, cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Thus, epidemiological studies show that the agonists of these receptors, nicotine and its derivatives contained in tobacco smoke, contribute to the onset and development of tumors of the lung [ 1 ], breast [ 3 , 63 ], pancreas [ 64 , 65 ], head and neck [ 66 ], accelerating proliferation and suppressing apoptosis. On the contrary, blockade of nAChRs slows tumor growth in experimental models of lung [ 21 , 22 ] and breast [ 18 , 20 ] cancer. The effect of nicotine is realized with the participation of nAChRs containing α7 [ 1 , 67 ], α9 [ 1 , 15 , 68 ] and α5 [ 1 , 2 , 16 ] subunits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, epidemiological studies show that the agonists of these receptors, nicotine and its derivatives contained in tobacco smoke, contribute to the onset and development of tumors of the lung [ 1 ], breast [ 3 , 63 ], pancreas [ 64 , 65 ], head and neck [ 66 ], accelerating proliferation and suppressing apoptosis. On the contrary, blockade of nAChRs slows tumor growth in experimental models of lung [ 21 , 22 ] and breast [ 18 , 20 ] cancer. The effect of nicotine is realized with the participation of nAChRs containing α7 [ 1 , 67 ], α9 [ 1 , 15 , 68 ] and α5 [ 1 , 2 , 16 ] subunits.…”
Section: Discussionmentioning
confidence: 99%
“…The role of nAChRs in non-neuronal cells is a subject of extensive studies, but it is already clear that these receptors are involved in the regulation of proliferation and migration of cancer cells [ 13 , 14 ], promote tumor formation [ 15 ] and enhance the resistance of tumor cells to apoptosis [ 14 , 16 , 17 ]. In addition, a number of experimental studies have shown a slowdown in tumor growth in vivo under the action of nAChR blockers such as α-conotoxins [ 18 , 19 , 20 ], α-cobrotoxin [ 21 ] and alkylpyridinium polymer APS8 [ 22 ]. However, the cytotoxic properties of nicotine, agonist of the most of nAChRs, against both normal [ 23 , 24 , 25 , 26 ] and tumor [ 27 ] cells are known.…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ channel blockers, such as amlodipine, induce G1 phase accumulation by alleviating Ca 2+ entry into A431 epidermoid cancer cells . Studies in lung and breast cancer cells, as well as chromaffin cells, have shown that activation of α7 subtype nAChRs results in an influx of Ca 2+ and activation of protein kinase C, followed by ERK and c-Myc, both increasing proliferation and inhibiting apoptosis and that antagonists can have the opposing effects. A specific α7 nAChR inhibitor potently elicited cell death in lung cancer cells, and this was linked to upregulation of the caspases 3, 8, and 9 . There is also evidence that, in the brain, nAChRs are linked to neuroprotection, preventing cell death.…”
Section: Resultsmentioning
confidence: 99%
“…APS8 can also block α4β2 nAChR, although its affinity for α7 nAChR is high. 69 Together with, MD-354 and compound 12, its N-methyl analogue containing a novel phenyl guanidine scaffold, were reported as noncompetitive α7 nAChR antagonists. 107,108 In the rat brain, compound 12 can compete [ 125 I]-bungarotoxin in the cerebral cortex, hippocampus, and hypothalamic mammillary nuclei, that express α7 nAChR.…”
Section: ■ the Development Of α7 Nicotinic Acetylcholine Receptor Ant...mentioning
confidence: 99%